Sistem Pendukung Keputusan Penerimaan Karyawan Menggunakan Metode SAW (Studi Kasus di PT. Nusantara Sakti Ciptadana Finance Kota Bengkulu) - Yupianti Yupianti; Sinta Puspita Sari (Jurnal Media Infotama, 2017)
The method used in this research was system development method. To collect data, interview and literature study was conducted. The software used to build the system was Visual Basic 6.0 and the results obtained were able to provide quick and accurate output. The results of this research was Decision Support System for Employees Recruitment. The system consist of five criteria, namely input for applicants, input for data criteria of administrative completeness, input for criteria of computer practice examination, input for written test criteria, input for weighting criteria, and data input for determining Final Calculation Value of Simple Additive Weight. There were also two reports, namely individual reports and rank reports. From the results of research, it can be concluded that the Decision Support System for Employees Recruitment at PT. Nusantara Sakti Ciptadana (NSC) Finance Kota Bengkulu Using SAW Method, were more efficient, complete and accurate.Keyword : Decision Support System, Simple Additive Weighting, SAW